"Are You Trying to Make Them Gay?": Culture Wars, Anxieties about Genderplay, and the Subsequent Impacts on Youth. (1st July 2021) - Dykstra, KJ; Litwiller, Fenton
Abstract: Using a queer theoretical lens, this conceptual paper explores the complexities of working with queer youth in leisure spaces by using genderplay to explore gender identity. Given the current social and political climate in Canada, researchers in this area face considerable professional road blocks from gatekeepers, despite providing often life-saving access for youth to queer mentors, community, and health resources. This paper, therefore, provides insight into the pervasiveness of the image of the child that informs the anxiety present in current political, social, and cultural discourses about queer children and the danger that image is putting these actual children in by limiting access to the above stated resources. Moreover, we expose how the image of the child is always invested in ideals of middle and upper-class whiteness, able-bodiedness, and imagined straightness from the outset, which further limits access to leisure spaces for queer children who may be otherwise marginalized.